Correction: Interpenetration of fractal clusters drives elasticity in colloidal gels formed upon flow cessation. Issue 40 (7th October 2022) - Dagès, Noémie; Bouthier, Louis V.; Matthews, Lauren; Manneville, Sébastien; Divoux, Thibaut; Poulesquen, Arnaud; Gibaud, Thomas
Abstract : Correction for 'Interpenetration of fractal clusters drives elasticity in colloidal gels formed upon flow cessation' by Noémie Dagès et al., Soft Matter, 2022, 18, 6645–6659, ; https://doi.org/10.1039/D2SM00481J .